Capital Abundance and Its Consequences for Trade Policy - Carl Christian von Weizsäcker (Intereconomics, 2019)
Protectionist moves may be countered by reference to the conundrum of capital scarcity. In a world in which unilateral imposition of trade barriers are a looming possibility, capital scarcity may nevertheless imply that free trade is a kind of Nash equilibrium.
Keywords: 330